Study on composite beams with prefabricated steel bar truss concrete slabs and demountable shear connectors. (1st May 2020) - Du, Hao; Hu, Xiamin; Meng, Yanfei; Han, Guohui; Guo, Kaikai
Highlights: A sustainable and prefabricated composite structural system was presented. Experimental researches on the demountable bolted connector were conducted. Experimental researches on the prefabricated composite beams were conducted. The model for predicting load carrying capacity of the composite beams was proposed. Abstract: In the conventional steel-concrete composite beams, the composite action is achieved by welded stud connectors which are encased into the cast-in-place concrete slab. This makes the deconstruction and reuse of the structural components almost impossible. A sustainable and prefabricated composite structural system was developed in this study wherein the steel beam is attached to the prefabricated steel-bars truss concrete slab using the demountable bolted connectors. Twelve push-out specimens were designed and tested to assess the shear behavior of the bolted connectors. The test results showed that the shear bearing capacity of the bolted connectors with the prefabricated steel-bars truss concrete slab increased 7.0% over that of the bolted connectors with the prefabricated normal concrete slab. Three full-scale composite beams with various shear connection ratios were constructed and loaded to failure. For direct comparison, a similar composite beam was constructed with the same section size and shear connectors, but using the cast-in-place concrete slab. The flexural capacity of the composite beams with 68% shear connection and full shear connection increased 9.8% and 15.8% compared to the composite beam with 46% shear connection, respectively. The mechanical behavior of the composite beam with the prefabricated concrete slab was comparable with that of the composite beam with cast-in-place concrete slab. The load carrying capacity of the composite beam can be predicted by the simplified model in Eurocode 4 and the plastic model.